Long-term efficacy of Rituximab in steroid dependent and frequent relapsing adult nephrotic syndrome - Omri Feder; Dana Amsterdam; Mohamad Ershed; Ayelet Grupper; Doron Schwartz; Orit Kliuk-Ben Bassat (BMC Nephrology)
Abstract Background Corticosteroids are highly efficient for treatment of minimal change disease (MCD), however a substantial number of patients become steroid dependent (SD) or frequent relapsing (FR). Response rate is lower in primary Focal Segmental Glomerulosclerosis (FSGS). Since prolonged exposure to corticosteroids should be avoided, an effective alternative is required. Rituximab is a promising agent. We aimed to evaluate the efficacy of Rituximab in adults with SD/FR nephrotic syndrome (NS). Methods A retrospective cohort study, evaluating patients with SD/FR NS treated with Rituximab in a tertiary hospital. Rituximab was given at induction, with additional doses subjected to the treating nephrologist decision. Primary outcome was number of relapses and time to first relapse. Safety was assessed. Results Twenty-one adults were included. Among them, 14 (66.7%) were diagnosed with MCD, 5 (23.8%) with FSGS, in 2 cases kidney biopsies were not performed. Median age was 54.6 years. Median follow up was 39.6 months. Number of relapses decreased significantly after Rituximab compared to before treatment (median relapses 0 compared to 3, respectively, W = 3.70, p <.001). Time to first relapse was significantly shorter before Rituximab compared to after (median 11 vs. 536 days, respectively, W = 3.05, p =.002). Hazzard Ratio for relapse was higher in patients who received one Rituximab course compared to those who received an additional maintenance (HR = 4.31, 95% CI: 1.13–16.39, p =.032). Treatment was well-tolerated, serious adverse events included cholecystitis and severe COVID-19. Conclusions Rituximab emerges as an efficient safe steroid sparing in patients with SD/FR NS, with longer remission achieved when an additional maintenance dose is given after the first course.